Exploration of key mechanisms underlying the therapeutic effects of AMD3100 on attenuating lipopolysaccharide-induced acute lung injury in mice - Zhou Lv; Bohan Zhang; Hui Zhang; Yanfei Mao; Qihong Yu; Wenwen Dong (PeerJ)
Context AMD3100, a CXCR4 antagonist, has beneficial effects immaculate in the treatment of acute lung injury (ALI). Objective ALI is a severe inflammatory condition associated with poor prognosis and limited treatment options. AMD3100, has therapeutic effects that reduce ALI. Our study explored the regulatory mechanisms of AMD3100 in alleviating the injury of lipopolysaccharide (LPS)-induced ALI in mice. Materials and Methods Male ICR mice were randomly divided into control, LPS-treated, AMD3100-treated, and LPS + AMD3100-treatment groups. The histological changes of lung tissues from different groups were evaluated using hematoxylin and eosin staining. Lung injury was measured by ELISA and lung wet/dry ratio. Moreover, lung tissues from the four groups were subjected to transcriptome sequencing followed by differential expression, functional enrichment, protein-protein interaction (PPI) networks, and transcription factor analyses. The validation of mRNAs and protein levels were conducted with qRT-PCR and ELISA. Results Hematoxylin and eosin staining combined with the concentration of IL-1 and IL1-β and lung wet/dry ratios revealed that AMD3100 reduced the level of LPS-induced lung injury. Analysis of the transcriptome sequencing data identified 294 differentially expressed genes in the LPS-induced ALI mouse model. Based on the PPI network and module analysis, hub targets of AMD3100, such as Cxcl10 and Cxcl9, were identified in module 1, and hub targets, such as Cxcl12 and Cxcl1, were identified in module 2. Cxcl10 and Cxcl9 are involved in the Toll-like receptor signaling pathway, and Cxcl12 and Cxcl1 arae enriched in the nuclear factor-kappa B signaling pathway. Cxcl19, Cxcl10, and Cxcl1 are targeted by transcription factors like NF-κB. The validation of mRNAs and protein levels conducted by PCR and ELISA supported our transcriptome data. Conclusions Our findings indicate that AMD3100 may exhibit a therapeutic effect on LPS-induced ALI in mice by modulating multiple chemokines to inhibit the Toll-like receptor/nuclear factor-kappa B signaling pathway.